Waktu Penyitaan Aset sebagai Determinan Efektivitas Pemulihan Kerugian Keuangan Negara: Analisis Ekonomi-Hukum terhadap Perkara Tindak Pidana Korupsi - Jaya, Indra; Slamet Tri Wahyudi; Supardi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The gap between state financial losses adjudicated and assets actually recovered in corruption cases is commonly attributed to institutional weaknesses or the absence of an Asset Forfeiture Act, while the temporal dimension of seizure is rarely examined. This article argues that the timing of seizure is the key operational determinant of state financial loss recovery. Two research questions are addressed: the normative construction of seizure across the stages of investigation, prosecution, and execution, and how seizure timing affects recovery effectiveness when analysed through Economic Analysis of Law, together with a reconstruction of relevant provisions. Using a juridical-normative method, the research combines comparative approaches, with Jiwasraya as the primary case study and Asabri, alongside comparisons with Singapore, South Korea, and Italy. The analysis identifies the investigation stage as the golden time for seizure because it offers the opportunity to preserve and recover assets, whereas the execution stage yields the lowest marginal benefit. The widening asset recovery gap between these stages can be interpreted as a social cost that may be reduced without changing the prevailing conviction-based system. Furthermore, the 2025 Criminal Procedure Code, the institutional consolidation of the Asset Recovery Agency, and Attorney General Guideline No. 7 of 2025 strengthen the role of the Public Prosecution Service as dominus litis in the asset recovery cycle. Five reconstruction proposals are formulated, most of which can be implemented within the existing legal framework.